ASSESSING STUDENTS' CONSECUTIVE INTERPRETING QUALITY (A CASE STUDY IN ENGLISH LITERATURE STUDY PROGRAM) - Ikrima Budiawati; O. Setiawan Djuharie; Andang Saehu (Journal of English Language Learning, 2022)
This research aims to assess the quality of students’ consecutive interpreting in terms accuracy, fluency, and acceptability in English Literature study program, Faculty of Adab and Humanities, UIN Sunan Gunung Djati Bandung. This research uses qualitative case study method with the results that shows 153 data from 10 students that have interpreted the messages consecutively. In terms of accuracy, there are 137 (89.56%) data were transferred accurately, 11 (7.18%) data were transferred less accurately, and 5 (3.26) data were transferred inaccurately. In terms of fluency, there are 125 (81.69%) data were transferred fluently, 25 (16.33%) data were transferred less fluently, and 3 (1.98%) data were not transferred fluently. Meanwhile, in terms of acceptability there are 128 (83.66%) data were transferred acceptable, 20 (13.07%) data were transferred less acceptable, and 5 (3.27%) data were transferred not acceptable. This research shows students are having considerable skill in interpreting the messages from source language into the target language consecutively. Keyword: Accuracy, Fluency, Acceptability